2013
DOI: 10.5750/ejpch.v1i2.665
|View full text |Cite
|
Sign up to set email alerts
|

Parent and staff perceptions of family-centred care in two Australian children’s hospitals

Abstract: Aim: This paper is a report of the comparison of perceptions of family-centred care by hospital staff (nurses, doctors and allied health staff) and parents of hospitalised children in two Australian tertiary paediatric hospitals.Background: Family-centred care is an accepted approach to caring for children and their families in hospital. Previous publications have been inconsistent, ranging from promoting its benefits and integration into practice, reporting operational difficulties and proposing that family-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
1
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 17 publications
7
44
1
19
Order By: Relevance
“…Several studies, completed and underway, are measuring health staff's attitudes to working with children and working with their parents [25][26][27][28]. To date, all have found that staff score working with children significantly more positively than working with their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, completed and underway, are measuring health staff's attitudes to working with children and working with their parents [25][26][27][28]. To date, all have found that staff score working with children significantly more positively than working with their parents.…”
Section: Discussionmentioning
confidence: 99%
“…• Do the Perceptions of Family Centered Care -Parent' (PFCC-P)' and the 'Perceptions of Family Centered Care -Staff (PFCC-S)' (Gill et al, 2013;Shields & Tanner, 2004) questionnaires work in rural and remote populations?…”
Section: Research Questionsmentioning
confidence: 99%
“…The tenets of centrality and importance of the family in child healthcare planning, make FCC an ideal model for a chronic paediatric condition such as CF (Kuhlthau et al, 2011). While studies have compared perceptions of FCC between parents and health professionals in the paediatric setting (Gill, Pascoe, Monterosso, Young, Burr, Tanner & Shields 2013), there have been no studies examining perceptions of FCC held by parents of children with CF in Australia or elsewhere.…”
mentioning
confidence: 99%
“…27,40 Similarly, in Jordan, parents within a critical care or oncology area reported mixed satisfaction scores for information, 35,41 and parents in an Australian general or neonatal area reported a higher perception than staff of FCC delivery. 42,43 In line with needs being met, significant differences (P < 0.05) were reported for 49 needs in Sweden, 25 44 needs in Australia 28 and 42 needs in England 26 when more staff than parents perceived that parents needed assistance, whereas in Iceland and New Zealand, more parents than staff perceived help was needed for 27 needs. 27,40 The difference in perceptions of needs being met or needed appeared to be influenced by the level of perceived importance of the need and the individual demographic variables.…”
Section: Discussionmentioning
confidence: 92%